In vitro Antioxidant Potential of Hyphaene thebaica Pulp Bioactive Fraction (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
Oxidative stress underlies the development of several chronic disorders, prompting interest in plant-based antioxidants with defined chemical composition and biological efficacy. This study investigated the antioxidant potential of Hyphaene thebaica pulp through integrated phytochemical quantification, spectroscopic characterization, chromatographic profiling, and in vitro antioxidant assays. The pulp exhibited measurable total phenolic content (19.90 ± 2.20 mg/g) and remarkably high total flavonoid content (615.94 ± 6.36 mg/g), indicating a substantial pool of redox-active metabolites. FTIR analysis of the aqueous fraction revealed characteristic absorption bands corresponding to hydroxyl, carbonyl, aliphatic, aromatic, nitro, and amine functional groups, supporting the presence of phenolics, flavonoids, fatty acids, and related antioxidant-associated constituents. GC–MS profiling identified compounds with reported antioxidant relevance, including oleic acid, tetradecanoic acid, long-chain aliphatic alcohols, and flavone-related structures, suggesting multiple antioxidant mechanisms. Antioxidant assays demonstrated solvent-dependent activity, with ethyl acetate extract showing the strongest DPPH radical scavenging activity (IC₅₀ = 4.19 ± 0.92 µg/mL), followed by chloroform and aqueous fractions, while the crude extract exhibited comparatively weaker activity. Total antioxidant capacity further confirmed superior activity of the ethyl acetate fraction (729.16 ± 3.21 µg/mL), indicating enrichment of potent antioxidants in semi-polar solvents. Collectively, the findings suggest that the antioxidant activity of H. thebaica pulp arises from the synergistic action of phenolic and flavonoid compounds alongside lipid-derived constituents, providing a mechanistic basis for its potential application as a natural antioxidant source.
Keywords: Oxidative stress; Plant-based antioxidant; Phytochemicals; Ultrasound-assisted extraction; Chromatography